Life history evolution and cellular mechanisms associated with increased size in high‐altitude Drosophila. Issue 16 (25th July 2016) - Lack, Justin B.; Yassin, Amir; Sprengelmeyer, Quentin D.; Johanning, Evan J.; David, Jean R.; Pool, John E.
Abstract: Understanding the physiological and genetic basis of growth and body size variation has wide‐ranging implications, from cancer and metabolic disease to the genetics of complex traits. We examined the evolution of body and wing size in high‐altitude Drosophila melanogaster from Ethiopia, flies with larger size than any previously known population. Specifically, we sought to identify life history characteristics and cellular mechanisms that may have facilitated size evolution. We found that the large‐bodied Ethiopian flies laid significantly fewer but larger eggs relative to lowland, smaller‐bodied Zambian flies. The highland flies were found to achieve larger size in a similar developmental period, potentially aided by a reproductive strategy favoring greater provisioning of fewer offspring. At the cellular level, cell proliferation was a strong contributor to wing size evolution, but both thorax and wing size increases involved important changes in cell size. Nuclear size measurements were consistent with elevated somatic ploidy as an important mechanism of body size evolution. We discuss the significance of these results for the genetic basis of evolutionary changes in body and wing size in Ethiopian D. melanogaster . Abstract : We investigate developmental mechanisms of size evolution in the largest known natural population of Drosophila melanogaster, from the highlands of Ethiopia. We find that large size did not result from extended larval development, but is associated with the production of fewer but larger eggs. We also find that both cell proliferation and cell size have contributed to enlarged wing and thoracic muscle cells.